The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1526602819860124
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Calcification as a Risk Factor for In-Stent Restenosis in Complex Femoropopliteal Lesions After Zilver PTX Paclitaxel-Coated Stent Placement

Abstract: Purpose: To evaluate the effect of vessel calcification on in-stent restenosis (ISR) after drug-coated stent (DCS) placement in the femoropopliteal segment. Materials and Methods: A retrospective multicenter study was undertaken involving 220 consecutive symptomatic patients (mean age 73.1±8.3 years; 175 men) with femoropopliteal lesions in 230 limbs treated with the Zilver PTX DCS and having duplex surveillance after the endovascular procedures. Mean lesion length was 16.4±9.8 cm (range 2–40); there were 104 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…In the prospective, multicenter ZEPHYR registry, 2,3 we demonstrated that lesion length 2 and the lack of cilostazol administration 3 were important risk factors for 1-year restenosis. Ichihashi et al 1 confirmed in their study that these factors increased the longer-term risk of patency loss, externally validating the clinical importance of the Zilver PTX in a different cohort. On the other hand, the clinical impact of vessel diameter seemed somewhat different between the ZEPHYR study and theirs.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…In the prospective, multicenter ZEPHYR registry, 2,3 we demonstrated that lesion length 2 and the lack of cilostazol administration 3 were important risk factors for 1-year restenosis. Ichihashi et al 1 confirmed in their study that these factors increased the longer-term risk of patency loss, externally validating the clinical importance of the Zilver PTX in a different cohort. On the other hand, the clinical impact of vessel diameter seemed somewhat different between the ZEPHYR study and theirs.…”
mentioning
confidence: 78%
“…Our ZEPHYR study showed that vessel diameters <4.5 mm, but not 4.5–6.0 mm, increased the risk of restenosis when compared to ≥6.0 mm. Ichihashi et al 1 reported a trend in the inverse relationship between vessel diameter and risk of restenosis (hazard ratio 0.8 per 1-mm increment), but the relationship did not reach statistical significance (p=0.138). The failure to detect a statistically significant difference might have come from the assignment of vessel diameter as a continuous variable or a small sample size (230 limbs).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…76 Additionally, calcification prevents the transfer of drugs to the arterial wall during DCB angioplasty and is a risk factor for worse outcomes. 7779 Intravascular lithoplasty (IVL) is a novel method of managing vascular calcification using acoustic shock waves, similar to lithotripsy which has been used to treat nephrolithiasis. The Shockwave Medical Peripheral Lithoplasty System (Shockwave Medical, Fremont, CA, USA) generates pulsatile mechanical energy that disrupts calcium while minimizing vessel trauma and allows low-pressure balloon angioplasty.…”
Section: New Devices For Revascularization In Cltimentioning
confidence: 99%